PEMANFAATAN LIMBAH ORGANIK BUNGA POTONG SEDAP MALAM SEBAGAI BAHAN PEMBUATAN KOMPOS DI DESA PEKOREN PASURUAN - Sri Rahayu, Yekti; ', Sunyoto; Maajid, Luqman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
Postharvest handling of cut flowers tuberose in the village of Pekoren, subdistrict Rembang, Pasuruan city, resulting in excessive volumes of organic waste, and it is not handled properly because of the knowledge and technology of the farmer is very limited. This program aims to process organic waste tuberose cut flower into compost as a soil conditioner and plant nutrient enhancer. The methods used is Partisipatory Rural appraisal (PRA) which involves group participation with tuberose flower growers group in training activities and demoplot composting. To process organic waste, supporting facilities and infrastructure that has been created is a composting and crop thrasher. Laboratory analysis indicates that the nutrient content of compost in accordance with the standards established by the Indonesian national standars which contain pH 7.4 (SNI maximum 7.49); Ntotal (%) 0.7 (SNI minimal 0.4); P (%) 0.3 (SNI minimal 0.10); K(%) 0.36 (SNI minimal 0.2); Ca (%) 7.21 (SNI maksimal 25.5); Mg (%) 0.63 (SNI maksimal 0.6); Fe(%) 1.1887 (SNI maksimal 2.00); Mn(%) 0.12 (SNI maksimal 0.1); Zn (mg/kg) 71.5 (SNI maksimal 500); S(%) 0.0108 (SNI minimal lebih dari atau sama dengan 0.01). while the result of testing the physical quality compost showed a dark brown color and insuble in water, compost smell like the smell of soil and compost temperature stable and equal to room temperature.